FV3-like ranavirus infection outbreak in black-spotted pond frogs (Rana nigromaculata) in China. (October 2018) - Mu, W.H.; Geng, Y.; Yu, Z.H.; Wang, K.Y.; Huang, X.L.; Ou, Y.P.; Chen, D.F.; He, C.L.; Zhong, Z.J.; Yang, Z.X.; Lai, W.M.
Abstract: In April 2016, an outbreak emerged in a cultured population of black-spotted pond frog tadpoles in Shuangliu County, China, whereas tadpoles were suffering from substantial mortality (90%). Principal clinical signs of diseased tadpoles were comprised haemorrhage on their body surface, swollen abdomen with yellow ascites, congestion and swelling of the liver. The diseased tadpole's homogenates tissue were inoculated into epithelioma papulosum cyprini (EPC) cells at 25 °C for 4 days which caused typical cytopathic effect, and the viral titer TCID50 reached 10 7 /0.1 mL. In pathogenicity tests, tadpoles were immersed in 2‰ virus fluid for 8 h, the clinical signs were observed similar to those recognized in naturally infected tadpoles and mortality rate were reached up to 80%, which affirms that the virus was the main cause for this disease. In addition, transmission electron microscopy of EPC cells infected with isolated virus reflected that the virus was in a regular hexagon way (shape) with capsule like structure. The diagonal diameter was recorded 135 ± 8 nm, wherever virus particles were arrayed in crystalline manner in the cytoplasm. The electrophoresis of MCP gene PCR-product showed that the samples of diseased tadpoles, aquaculture water source and isolated virus were all positive. The sequence of the isolate revealed more than 99% similarities to ranavirus based on homology and genetic evolution analysis of the whole MCP gene, and the isolate belongs to FV3-like virus group. This study confirmed that ranavirus was the causative agent of this outbreak, and named the virus as Rana nigromaculata ranavirus (RNRV). Highlights: This is the first report of a ranaviral infection affecting Rana nigromaculata in China. The isolated virus ( Rana nigromaculata ranavirus, RNRV) can induce a high mortality in Rana nigromaculata by natural or artificial infection. The RNRV belongs to FV3-like ranaviruses genogroup by MCP genes sequences analysis.